2015
DOI: 10.1159/000431088
|View full text |Cite
|
Sign up to set email alerts
|

Head Lift Exercise Improves Swallowing Dysfunction in Spinal and Bulbar Muscular Atrophy

Abstract: Background: Dysphagia due to bulbar involvement is a major symptom of patients with spinal and bulbar muscular atrophy (SBMA). The aim of this pilot study was to test the efficacy and safety of the head lift exercise for swallowing dysfunction in SBMA. Methods: We enrolled 6 subjects with genetically confirmed SBMA and instructed them to perform the head lift exercise for 6 weeks. The efficacy outcome measures were the changes from baseline in tongue pressure, the scores of swallowing functional questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Given that the presence of pharyngeal residue is the most common finding in SBMA patients and a laryngeal penetration risk exists even in those without subjective dysphagia, we recommend the chin‐tuck maneuver and the effortful swallow as safe methods of swallowing for all SBMA patients with dysphagia 36, 37. We also reported that a 6‐week head lift exercise may improve swallowing dysfunction as measured by tongue pressure 38. Reinforcement of compensatory swallowing mechanisms may lead to effective rehabilitation in dysphagia patients.…”
Section: Discussionmentioning
confidence: 89%
“…Given that the presence of pharyngeal residue is the most common finding in SBMA patients and a laryngeal penetration risk exists even in those without subjective dysphagia, we recommend the chin‐tuck maneuver and the effortful swallow as safe methods of swallowing for all SBMA patients with dysphagia 36, 37. We also reported that a 6‐week head lift exercise may improve swallowing dysfunction as measured by tongue pressure 38. Reinforcement of compensatory swallowing mechanisms may lead to effective rehabilitation in dysphagia patients.…”
Section: Discussionmentioning
confidence: 89%
“…It is increasingly recognized that non-neurological features of the disease have an equally important impact on the patients' quality of life ( 3 , 31 34 , 87 , 88 , 91 , 92 ). Until now, clinical trials on SBMA focused almost exclusively on the treatment of motor symptoms ( 14 , 45 , 47 , 51 53 , 55 , 57 , 68 , 92 , 93 ), but a shift to targeted molecular therapies ( 94 ) and focus on systemic processes are likely to be witnessed in the near future. From a clinical trial perspective, ideal biomarkers should undergo robust validation, sensitivity and specificity profiling, and sampling and measurement harmonization across different centers.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…In SBMA, VF can reliably detect the impairment of the oral phase of deglutition confirming large amount of oral barium residue ( 56 ). VF has been previously used in clinical trials ( 51 , 55 , 68 ), but the lack of standardization makes it less suitable for robust multicenter studies.…”
Section: Biomarkers Of Neurological Involvement In Sbmamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a sequence of head-lift exercises has been proposed as it seems to ameliorate swallowing dysfunction [99]. This hypothesis has been tested in six patients with good results but needs to be confirmed in larger and longitudinal trials.…”
Section: Experimental Treatmentsmentioning
confidence: 99%